Être ou ne pas être subversives ? - Dominique Bourque (Genre, Sexualité et Société)
The preliminary results of an Internet survey conducted among French Canadian young lesbians indicate, notably, that the majority of the 362 respondents see themselves through the apparatus of sex and sexual difference rather than through the expected de/constructivist perspective, associated with the Postmodern era. Is this a consequence of the hypersexualisation of young women in the medias and the pornographisation of popular culture? Can it be a survival strategy in a backlash context that masks (non factice) lesbianism? Or is it a position of retreat induced by the multiple discriminations this social group is facing in terms of sex, sexuality, language, culture and, in the case of those who belong to a so called visible or status minority, “race” and citizenship?